European guidelines for validating non-formal and informal learning - (:unkn) unknown (Publications Office of the European Union, 2023)
"The European guidelines for validation of non-formal and informal learning seek to clarify the conditions for developing and implementing validation. The guidelines are written for everybody involved in initiating, developing and implementing validation and are meant as a source of inspiration and reflection. The development and implementation of validation relies on several interconnected elements that, when combined, can strengthen the role of validation at national and European levels. The guidelines put the individual at the heart of the process, responding to needs and objectives. They provide insights into validation provision and methodologies and how the process can be coordinated and carried out. This third update of the European guidelines follows and expands the principles agreed in the 2012 Council Recommendation on validation, and considers the evaluation of the Recommendation and follow-up. The guidelines are the result of consultation with stakeholders and validation experts during the last 3 years." (Editor ; BIBB-Doku)
Keywords: S 2.2.4.4 Anerkennung non-formaler Qualifikationen; G 2.2.4 Lebensbegleitendes & lebenslanges Lernen; I 2.2 Europa; 370; 300; Erwachsenenbildung; Informelles Lernen; Erfahrungswissen; Anerkennung; Europa; Lebenslanges Lernen